Incorporação de titânio na peneira molecular Mor e suas propriedades - Fernandez, Romilda (2003)
The titanium incorporation in the MFI structure generated a new material, called TS-1, which showed highly active in oxidation reactions of organic compounds. A very important aspect in this titanium-silicate is that it can be used as catalytic for the oxidation in liquid phase with H2O2 as oxidant. However, the TS-1 possesses small pore diameter, which limits its application to molecules with kinetic diameter less than 5,5Å. This limitation has stimulated several investigators to study the incorporation of titanium into molecular sieves with larger pore diameter. This work has as purpose the incorporation of titanium into the structure MOR; verify the influence of the increase of the Si/Al ratio, the titanium content and source in the physical-chemical properties of this material; and finally verify the influence in the catalytic selectivity and activity in the oxidation of ciclo-hexeno with H2O2 as oxidant. The maximum Si/Al ratio in the samples of Ti-MOR prepared was of 10.5. The samples synthesized with TEOT as Ti source presented higher titanium contents in the solid that the samples synthesized with H2TiF6. The morphology of all the samples was in the form of needles. The IR spectra present a band at 960 cm-1, which was related to framework defects and not to Ti incorporation, as stated by other authors. The samples synthesized with H2TiF6 presented greater amount of pentacoordinated Ti atoms in the framework and a superior specify activity, compared to the samples synthesized with TEOT. Compared to TS-1, Ti-MOR presented higher activity in cyclohexene oxidation, however they are less selective to the epoxide.